Catalytic Friedel–Crafts C−H Borylation of Electron‐Rich Arenes: Dramatic Rate Acceleration by Added Alkenes. Issue 13 (28th February 2017) - Yin, Qin; Klare, Hendrik F. T.; Oestreich, Martin
Abstract: In the electrophilic C−H borylation of electron‐rich aromatic compounds with catecholborane, the catalytic generation of the boron electrophile is initiated by heterolysis of the B−H bond by various Lewis and Brønsted acids, with a boronium ion formed exclusively. After ligand dissociation, the corresponding borenium ion undergoes regioselective electrophilic aromatic substitution on aniline derivatives as well as nitrogen‐containing heterocycles. The catalysis is optimized using B(C6 F5 )3 as the initiator and proceeds without the addition of an external base or dihydrogen acceptor. Temperatures above 80 °C are generally required to secure efficient turnover in these Friedel–Crafts‐type reactions. Mechanistic experiments reveal that regeneration of the boronium/borenium ion with dihydrogen release is rate‐determining. This finding finally led to the discovery that, with added alkenes, catalytic C−H borylations can, for the first time, be carried out at room temperature. Abstract : Be positive : B(C6 F5 )3 initiates the acceptor‐free electrophilic aromatic substitution of anilines and azoles (and thiophenes) with catecholborane (catBH). Elevated reactions temperatures are required to overcome the rate‐determining step—the regeneration of the boronium/borenium ion. The addition of alkenes, for example, norbornene (nbe), changes the situation dramatically, with the reaction occurring at ambient temperature. PG=protecting group.